Manajemen Asma Pada Pasien Asma Bronkial Dengan Masalah Bersihan Jalan Napas Tidak Efektif - Syokumawena, Syokumawena; Mediarti, Devi; Safitri, Nova (JKM : Jurnal Keperawatan Merdeka, 2025)
Background : Bronchial asthma is a chronic inflammatory disease of the airways characterized by reversible airway obstruction. One of the most common nursing problems encountered during an acute asthma attack is ineffective airway clearance due to mucus hypersecretion and bronchospasm. Prompt and targeted nursing interventions are essential to prevent respiratory complications. Method : The design of this writing uses a descriptive method in the form of a case study. The Nursing Care Approach consists of assessment, nursing diagnosis, planning, implementation, evaluation, and nursing documentation. Results : All fourth patients demonstrated significant clinical improvement after interventions. Respiratory rate decreased, wheezing was reduced, cough became more effective, and oxygen saturation improved to ≥ 95%. These outcomes indicate that the nursing interventions were successful in resolving the ineffective airway clearance problem. Conclusion : Prompt and appropriate nursing interventions are effective in managing ineffective airway clearance in patients with bronchial asthma. A combination of non-pharmacological techniques and collaborative therapies plays a crucial role in improving respiratory status in emergency care settings.